Primary Lung Metastases in Pediatric Malignant Non-Wilms Renal Tumors: Data from SIOP 93-01/GPOH and SIOP 2001/GPOH - Warmann, S. W.; Nourkami, N.; Frühwald, M.; Leuschner, I.; Schenk, J.-P.; Fuchs, J.; Graf, N. (Klinische Pädiatrie, 2012)
Malignant non-Wilms renal tumors (NWRT) are a small but relevant subgroup of renal neoplasms in children. In this study we analyzed corresponding data from the trials SIOP 93-01/GPOH and SIOP 2001/GPOH of the Society of Pediatric Oncology and Hematology.Data of 22 patients with NWRT and primary lung metastases were retrospectively reviewed. Analyses included epidemiology, tumor characteristics, chemotherapy, local treatment, and outcome.The following diagnoses were registered: Malignant Rhabdoid tumor of the kidney (MRTK, n=15), Renal-cell carcinoma (RCC, n=3), Clear-cell sarcoma of the kidney (CCSK, n=3), and primitive neuro ectodermal tumor (PNET, n=1). Median age of patients at diagnosis was 14 months. Overall survival was 36.36% (8/22). Of the 15 children with MRTK 3 survived, 3/3 patients with RCC, 1/3 patients with CCSK, and 1/1 patient with PNET survived. Lung metastases disappeared in 6 patients after initial chemotherapy, 6/8 patients undergoing local treatment of lung metastases (surgery, irradiation, or both) achieved complete remission. Only patients with complete clearance of lung lesions, either through neoadjuvant chemotherapy or subsequent local treatment, survived. Mean Follow up was 31 months (1–137).Survival of patients with stage IV NWRT is dismal. Complete removal of lung metastases seems mandatory for survival. An aggressive diagnostic and therapeutic approach seems justified in affected children.
Keywords: pediatric tumors; non-Wilms renal tumors; lung metastases; local treatment